The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1038/s41467-023-43470-1
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved proteomic profiling reveals compositional and functional transitions across the stress granule life cycle

Shuyao Hu,
Yufeng Zhang,
Qianqian Yi
et al.

Abstract: Stress granules (SGs) are dynamic, membrane-less organelles. With their formation and disassembly processes characterized, it remains elusive how compositional transitions are coordinated during prolonged stress to meet changing functional needs. Here, using time-resolved proteomic profiling of the acute to prolonged heat-shock SG life cycle, we identify dynamic SG proteins, further segregated into early and late proteins. Comparison of different groups of SG proteins suggests that their biochemical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 105 publications
(143 reference statements)
0
8
0
Order By: Relevance
“…Further comparison against a list of early and late stress granules markers (Hu et al, 2023) identified a further 16 SG markers, of which most were categorised as late SG markers. Therefore, 30% (40/134 proteins) of our SG preparation consisted of known SG markers (Hu et al, 2023; Jain et al, 2016). There were 17 proteins comparatively depleted in the SG fraction from the NEFH-TDP-43 mouse brains, when compared to the control mice (control/TDP = fold change >1.5, p<0.05) (Supplementary Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Further comparison against a list of early and late stress granules markers (Hu et al, 2023) identified a further 16 SG markers, of which most were categorised as late SG markers. Therefore, 30% (40/134 proteins) of our SG preparation consisted of known SG markers (Hu et al, 2023; Jain et al, 2016). There were 17 proteins comparatively depleted in the SG fraction from the NEFH-TDP-43 mouse brains, when compared to the control mice (control/TDP = fold change >1.5, p<0.05) (Supplementary Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Following comparison with the mammalian SG proteome (Jain et al, 2016), 24 of our 134 enriched proteins were known SG markers (Supplementary Table 2). Further comparison against a list of early and late stress granules markers (Hu et al, 2023) identified a further 16 SG markers, of which most were categorised as late SG markers. Therefore, 30% (41/134 proteins) of our SG preparation consisted of known SG markers (Hu et al, 2023; Jain et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations